2006
DOI: 10.1007/s10508-006-8997-z
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Sexual Arousal in Response to Erotica: Effects of Gender, Guided Fantasy, Erotic Stimulus, and Duration of Exposure

Abstract: This study was designed to evaluate the effects of gender, guided fantasy, erotic stimulus (with or without audio), and exposure duration on the subjective sexual arousal of participants watching a 10-min erotic video excerpt depicting sexual activities between a heterosexual adult couple. The excerpt was shown to 105 male and 110 female undergraduates, and sexual arousal was measured four times, at intervals of 1, 4, 7, and 10,min from the onset of the excerpt. While no erotic stimulus effect was found, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Recent research comparing subjective sexual arousal during different time intervals and different length video clips have demonstrated that subjective sexual arousal increased with length of film stimuli (Pfaus, 2008;Youn, 2006) and that genital response increased with stimulus intensity (Laan, Everaerd, van der Velde et al, 1995). The continuous 15 min period of explicit audiovisual sexual stimuli used in this study may have allowed for higher levels of sexual arousal that are more akin to the natural pattern of sexual response than shorter time periods.…”
Section: Discussionmentioning
confidence: 79%
“…Recent research comparing subjective sexual arousal during different time intervals and different length video clips have demonstrated that subjective sexual arousal increased with length of film stimuli (Pfaus, 2008;Youn, 2006) and that genital response increased with stimulus intensity (Laan, Everaerd, van der Velde et al, 1995). The continuous 15 min period of explicit audiovisual sexual stimuli used in this study may have allowed for higher levels of sexual arousal that are more akin to the natural pattern of sexual response than shorter time periods.…”
Section: Discussionmentioning
confidence: 79%
“…Janssen, Carpenter, and Graham (2003) found significant differences in self-reported sexual arousal to different erotic film clips, such that men reported much higher levels of arousal to male-selected film clips than did women. Youn (2006) recently reported sex differences in subjective sexual arousal to an erotic video, regardless of presence or absence of guided imagery, supporting the contention that men are more psychosexually responsive to visual erotic material than are women. Hamann, Herman, Nolan, and Wallen (2004) found that certain brain regions involved in the processing of appetitive, emotional, and biologically salient stimuli (the amygdala and hypothalamus) were more activated in men than in women when viewing visual erotic stimuli.…”
Section: Introductionmentioning
confidence: 83%
“…Men are more likely than women to engage in extradyadic sex Atkins et al 2001;Glass and Wright 1985;Oliver and Hyde 1993;Petersen and Hyde 2010;Thompson 1983;Wiederman 1997 Men are more likely than women to be sexually unfaithful multiple times with different sexual partners Blumstein and Schwartz 1983;Brand et al 2007;Hansen 1987;Laumann et al 1994;Lawson and Samson 1988;Spanier and Margolis 1983 Men are more likely than women to seek short-term sex partners that are already married Davies et al 2007;Jonason et al 2009;Parker and Burkley 2009;Schmitt and Buss 2001; Men are more likely than women to have sexual fantasies involving short-term sex and multiple opposite-sex partners Ehrlichman and Eichenstein 1992;Ellis and Symons 1990;Jones and Barlow 1990;Leitenberg and Henning 1995;Rokach 1990 Men are more likely than women to pay for short-term sex with (male or female) prostitutes Burley and Symanski 1981;Mitchell and Latimer 2009;Symons 1979 Men are more likely than women to enjoy sexual magazines and videos containing themes of short-term sex and sex with multiple partners Hald 2006; Koukounas and McCabe 1997;Malamuth 1996;Murnen and Stockton 1997;Salmon and Symons 2001;Youn 2006 Men are more likely than women to desire, have, and reproductively benefit from multiple mates and spouses Bereczkei and Csanaky 1996;Betzig 1986;Jokela et al 2010;Perusse 1993;Stone et al 2005;Zerjal et al 2003…”
Section: Empirical Findingsmentioning
confidence: 99%